Parental Involvement in Supporting Children's Independence and Providing a Balanced Understanding of Gender - Sapan, Erwin Bunga; Musrini, Isobeliana (Aṭfālunā Journal of Islamic Early Childhood Education, 2024)
This study explores parental involvement in supporting children's independence and providing a balanced understanding of gender from an early age. This research uses a qualitative approach with a case study for parents at SILO Makale Kindergarten, South Sulawesi. Data is collected through interviews, observation, and documentation. The results showed that the involvement of supportive parents, especially those who care about gender equality, positively impacts the development of children's independence and gender understanding. Children raised with gender-responsive parenting tend to be more independent and have a more balanced understanding of gender. However, children with less parental attention and involvement showed higher dependency on daily activities. In addition, this study revealed that gender education at the preschool level has not been implemented optimally, potentially affecting the development of children's understanding of gender roles. Based on the results of this study, it is recommended that parents be more actively involved in education and parenting that supports gender equality, as well as creating an environment that supports children's independence. It is also important for preschool education institutions to start systematically introducing the concept of gender equality.